2003
DOI: 10.1002/pca.706
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical fluid extraction of naringin from the peel of Citrus paradisi

Abstract: The highest yield (14.4 g/kg) of naringin, the major flavonoid from the peel of Citrus paradisi L., that could be achieved by supercritical fluid extraction was obtained using supercritical carbon dioxide modified with 15% ethanol and fresh (rather than dried) peels at 95 bar and 58.6 degrees C. This yield is higher than that attained by the conventional technique of maceration, and close to those obtained by reflux and Soxhlet methods. Furthermore, supercritical fluid extraction consumes less solvent and prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(46 citation statements)
references
References 10 publications
1
44
0
1
Order By: Relevance
“…Saldaña et al (1999) extracted purine alkaloids (caffeine, theobromine, and theophylline) from Ilex paraguaryensis (herbal maté tea) using SFE at 313-343 K temperature and pressure from 14-24 MPa. Supercritical CO 2 modified with ethanol (15 wt.%) gave higher extraction yields of naringin (flavonoid) from citrus paradise than pure supercritical carbon dioxide at 9.5 MPa and 58.6°C (Giannuzzo et al, 2003). Polyphenols and procyanidins were extracted from grape seeds using SFE, where methanol was used as modifier and methanol modified CO 2 (40%) released more than 79% of catechin and epicatechin from grape seed (Khorassani and Taylor, 2004).…”
Section: Supercritical Fluid Extraction (Sfe)mentioning
confidence: 99%
“…Saldaña et al (1999) extracted purine alkaloids (caffeine, theobromine, and theophylline) from Ilex paraguaryensis (herbal maté tea) using SFE at 313-343 K temperature and pressure from 14-24 MPa. Supercritical CO 2 modified with ethanol (15 wt.%) gave higher extraction yields of naringin (flavonoid) from citrus paradise than pure supercritical carbon dioxide at 9.5 MPa and 58.6°C (Giannuzzo et al, 2003). Polyphenols and procyanidins were extracted from grape seeds using SFE, where methanol was used as modifier and methanol modified CO 2 (40%) released more than 79% of catechin and epicatechin from grape seed (Khorassani and Taylor, 2004).…”
Section: Supercritical Fluid Extraction (Sfe)mentioning
confidence: 99%
“…Selection of supercritical fluids is very important for proper functioning of this process and a wide range of compounds can be used as solvents in this technique (Sihvonen et al 1999). Giannuzzo et al (2003) found that SC-CO 2 modified with ethanol gave higher extraction yields of naringin (flavonoid) from citrus waste than pure SC-CO 2 at 9.5 MPa and 58.6 °C. Ashraf-Khorassani and Taylor (2004) extracted polyphenols and procyanidins from grape seeds using SFE, where, methanol was used as modifier and methanol modified CO 2 (40%) released more than 79% of catechin and epicatechin from grape seed.…”
Section: Supercritical Fluid Extractionmentioning
confidence: 99%
“…solvent extraction (Anagnostopoulou et al 2006;Jeong et al 2004), hot water extraction (Xu et al 2008), alkaline extraction (Bocco et al 1998), resin based extraction (Kim et al 2007), enzyme assisted extraction (Li et al 2006), electron beam and gamma irradiation based extractions (Kim et al 2008) and supercritical fluid extraction (Giannuzzo et al 2003). Both conventional and more innovative extraction techniques may either cause the degradation of the targeted compounds due to high temperature and long extraction times as in solvent extractions, or pose some health related risks due to the unawareness of safety criteria during irradiation.…”
Section: Introductionmentioning
confidence: 99%